2019
DOI: 10.1002/jemt.23288
|View full text |Cite
|
Sign up to set email alerts
|

Surface ultrastructural descriptions of the oropharyngeal cavity of Anas querquedula

Abstract: The current work considers the first anatomical description of oropharyngeal cavity of Garganey, which was performed on eight heads with the help of scanning electron microscopy (SEM). The round apex of elongated tongue has anterior spatula‐like named lingual nail. SEM of dorsal surface of lingual nail carry microtubercles and micropores on its rostral part, while its caudal part carry numerous microridges and micropores, while lateral apical surface only without lingual nail carrying filiform papillae, but it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The tongue divided into three regions; apex, body, and root, identical to what was described in formerly published data (Abumandour, 2014a;Abumandour, 2018 Harmonious with these gross oversights, SEM imagery display that the round apex observed in all studied five developmental agestages, analogous to that noted in the goose, duck, quail and Egyptian laughing dove (Abumandour, Bassuoni, & Hanafy, 2019;Jackowiak et al, 2011;Parchami et al, 2010). The formerly published data described the presence of numerous appearance of the apex which were thought that it is correlated with the feeding style of the different feeding avian species such as; the oval apex in Hume's tawny owl (Abumandour & El-Bakary, 2017b), the pointed apex in the chicken, zebra finch and hoopoe Iwasaki & Kobayashi, 1986), the blunt apex (El-Mansi et al, 2020), the bifurcated apex note in the owl, Eurasian Hobby, house sparrow, and seagull (Abumandour, 2014a;Abumandour, 2018;Abumandour & El-Bakary, 2017b;Gewaily & Abumandour, 2020;Onuk et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…The tongue divided into three regions; apex, body, and root, identical to what was described in formerly published data (Abumandour, 2014a;Abumandour, 2018 Harmonious with these gross oversights, SEM imagery display that the round apex observed in all studied five developmental agestages, analogous to that noted in the goose, duck, quail and Egyptian laughing dove (Abumandour, Bassuoni, & Hanafy, 2019;Jackowiak et al, 2011;Parchami et al, 2010). The formerly published data described the presence of numerous appearance of the apex which were thought that it is correlated with the feeding style of the different feeding avian species such as; the oval apex in Hume's tawny owl (Abumandour & El-Bakary, 2017b), the pointed apex in the chicken, zebra finch and hoopoe Iwasaki & Kobayashi, 1986), the blunt apex (El-Mansi et al, 2020), the bifurcated apex note in the owl, Eurasian Hobby, house sparrow, and seagull (Abumandour, 2014a;Abumandour, 2018;Abumandour & El-Bakary, 2017b;Gewaily & Abumandour, 2020;Onuk et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…The present study revealed freely distributed papillae on the laryngeal mound, and around the infundibular cleft, in addition to 6 rows of caudally directed papillae from the papillary crest until a transverse row of pharyngeal papillae caudal to the infundibular cleft. However, the presence of the pharyngeal papillae was reported in many avian species (Abumandour et al., 2019; Abumandour & El‐Bakary, 2017a, 2017b), they were absent in ratite (Crole & Soley, 2010a). The presence of these caudally directed papillae either distributed or arranged in rows considered as an adaptive mechanism for the hooded crow that may help in directing the food particles caudally towards the oesophagus and prevent regurgitation (Moussa & Hassan, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…This result recorded also in owl (Abumandour & El‐Bakary, 2017b; Emura, Okumura, & Chen, 2009), falcon and kestrel (Emura et al., 2008), nutcracker (Jackowiak et al, 2010), house sparrow (Abumandour, 2018), seagull (Onuk et al., 2013) and Eurasian Hobby (Abumandour, 2014). The pointed lingual apex appeared in chicken (Iwasaki & Kobayashi, 1986) and zebra finch (Dehkordi et al., 2010), while the oval lingual apex appeared in Common kestrel ( Falco tinnunculus ) (Abumandour & El‐Bakary, 2017b), but the round lingual apex appeared in goose, duck and quail (Emura, 2009a; Jackowiak et al., 2011; Parchami et al., 2010a), hoopoe (Abumandour & Gewaily, 2019a) and some migratory birds (Abumandour et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations